Pengaruh Metode Brainstorming Terhadap Keaktifan Belajar Siswa pada Mata Pelajaran Pendidikan Agama Kristen di SMP Negeri 1 Saipar Dolok Hole Tahun Pembelajaran 2023/2024 - Dian Lorensa Ritonga; Raikhapoor Raikhapoor; Julita Herawati; Sandy Ariawan; Goklas J. Manalu (CV. Alim's Publishing, 2024)
The research aims to determine the positive influence of the brainstorming method on students' active learning in Christian Religious Education subjects at SMP Negeri 1 Saipar Dolok Hole for the 2023/2024 academic year. The research hypothesis is that there is a positive influence between the brainstorming method on students' active learning in Christian Religious Education subjects at SMP Negeri 1 Saipar Dolok Hole for the 2023/2024 academic year. The population of all students at SMP Negeri 1 Saipar Dolok Hole for the 2023/2024 academic year who are Protestant Christians is 46 people. This research is population research. The research instrument is a closed questionnaire. The results of data analysis obtained: The value rcount=0.535>rtable=0.291 shows that there is a positive relationship between the brainstorming method and students' active learning in Christian Religious Education subjects. Regression equation. Hypothesis test Fcount=17.68>Ftable=3.23 then H0 (null hypothesis) is rejected and Ha (alternative hypothesis) is accepted. The research concluded that there was a positive and significant influence between the brainstorming method on students' active learning in Christian Religious Education subjects at SMP Negeri 1 Saipar Dolok Hole for the 2023/2024 academic year.